Metachronous Sudden Sensorineural Hearing Loss: Patient Characteristics and Treatment Outcomes. (28th January 2020) - Cooper, Timothy; Dixit, Ronak; Hobson, Candace E.; Hirsch, Barry E.; McCall, Andrew A.
Abstract : Objectives: Idiopathic sudden sensorineural hearing loss (ISSNHL) is a distressing condition that can significantly affect quality of life. Unilateral ISSNHL, occurring first in 1 ear and then the contralateral ear at a separate and discrete time, is a rare presentation that we refer to as metachronous ISSNHL . Our objective was to characterize the presentation of metachronous ISSNHL and report on management and hearing outcomes. Study Design: Retrospective case series. Setting: Otology clinic at an academic tertiary referral center. Subjects and Methods: Patients ≥18 years old presenting with metachronous ISSNHL between April 2008 to November 2017 were identified through review of the clinic electronic medical record. Metachronous ISSNHL was defined as unilateral ISSNHL occurring in temporally discrete episodes (>6 months apart) affecting both ears. Patients with identifiable causes for sudden hearing loss were excluded. Patient demographics, comorbidities, management, and audiologic outcomes were recorded. Results: Eleven patients with metachronous ISSNHL were identified out of 558 patients with ISSNHL. In patients with metachronous ISSNHL, the mean ± standard deviation age at the time of ISSNHL in the second ear was 58.6 ± 15.2 years (range, 31‐77 years). The mean interval between episodes was 9.6 ± 7.5 years (range, 1‐22 years). Patients were treated with systemic and intratympanic steroids with variable hearing recovery; 5 patients with resultant bilateral severe to profound hearing loss underwent successful cochlear implantation. Conclusion: Metachronous ISSNHL is uncommon. Treatment is similar to ISSNHL, and cochlear implantation can successfully restore hearing in individuals who do not experience recovery.